2017
DOI: 10.1038/emi.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization ofListeriaspecies from rodents in natural environments in China

Abstract: Listeria is ubiquitous in a variety of environments and can be isolated from a wide range of animal hosts. Rodents are capable of carrying pathogenic bacteria in their intestines, such as Listeria, and can disseminate those pathogens into the natural environment and to where human activity occurs. In this study, we investigated the occurrence and antimicrobial susceptibility of Listeria spp. isolated from wild rodents found in natural environments in China. We collected 341 intestinal fecal samples of rodents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 44 publications
3
43
0
2
Order By: Relevance
“…The prevalence of L. monocytogenes in our study (36%) was noticeably higher than in most other wildlife surveys, where prevalence ranged from 0.3% to 18% (Hayashidani et al , ; Lyautey et al , ; Wacheck et al , ; Nowakiewicz et al , ; Weindl et al , ; Wang et al ., ; Cao et al , ;). Only two wildlife studies, involving urban birds in Finland and France, respectively, yielded prevalence levels of 33–36% (Bouttefroy et al , ; Hellstrom et al , ), similar to what we found in the bears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of L. monocytogenes in our study (36%) was noticeably higher than in most other wildlife surveys, where prevalence ranged from 0.3% to 18% (Hayashidani et al , ; Lyautey et al , ; Wacheck et al , ; Nowakiewicz et al , ; Weindl et al , ; Wang et al ., ; Cao et al , ;). Only two wildlife studies, involving urban birds in Finland and France, respectively, yielded prevalence levels of 33–36% (Bouttefroy et al , ; Hellstrom et al , ), similar to what we found in the bears.…”
Section: Discussionmentioning
confidence: 99%
“…has rarely been found in other wildlife studies, where in fact the opposite was frequently observed, with L. monocytogenes tending to be noticeably less common than other Listeria spp. (Innoue et al, 1992;Quessy and Messier, 1992;Yoshida et al, 2000;Hellstr€ om et al, 2008;Wang et al, 2017;Cao , 2019). Only one study of rectal swabs from red fox, beech marten and raccoons in Poland found that, even though overall Listeria prevalence was low (approx.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) in China, Listeria spp. was detected in 31 of 341 intestinal rodent faeces, 11 of which were a detection of L. monocytogenes , specifically . Of these Listeria spp., 94.1% were resistant to oxacillin and 70.6% were resistant to cefuroxime .…”
Section: Discussionmentioning
confidence: 99%
“…was detected in 31 of 341 intestinal rodent faeces, 11 of which were a detection of L. monocytogenes , specifically . Of these Listeria spp., 94.1% were resistant to oxacillin and 70.6% were resistant to cefuroxime . In addition to potential environmental sources of L. monocytogenes , more information is needed regarding the role of guinea pig consumption and storage and care of guinea pigs in these communities in terms of hygiene and potential contamination in the home.…”
Section: Discussionmentioning
confidence: 99%
“…are commonly found in natural environments such as soils, sewage, surface water, wastewater sludge, vegetation, excrements and animal faeces (Lyautey et al ). The genus Listeria consists of 17 species including L. monocytogenes , L. innocua , L. welshimeri , L. ivanovii , L. seeligeri , L. grayi , L. marthii , L. fleischmannii , L. floridensis , L. rocourtiae , L. weihenstephanensis , L. cornellensis , L. aquatica , L. riparia , L. grandensis , L. booriae and L. newyorkensis (Wang et al ).…”
Section: Introductionmentioning
confidence: 99%